2014
DOI: 10.1007/s11655-014-1860-0
|View full text |Cite
|
Sign up to set email alerts
|

Andrographolide as an Anti-H1N1 drug and the mechanism related to retinoic acid-inducible gene-I-like receptors signaling pathway

Abstract: The RLRs mediated viral recognition provided a potential molecular target for acute viral infections and andrographolide could ameliorate H1N1 virus-induced cell mortality. And the antiviral effects might be related to its inhibition of viral-induced activation of the RLRs signaling pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 21 publications
1
28
0
Order By: Relevance
“…These observations were consistent with a previous study, which showed that sesamin downregulated p38 and JNK MAPK signaling pathways via IL-1β-induced human articular chondrocytes (Phitak et al 2012). Moreover, a recent report has shown that andrographolide inhibited the H1N1-infected cell model, while using the H1N1-infected respiratory epithelial cells and coculturing with the immunological cells including the dendritic cells, macrophage, and monocytes, via the RIG-I-like receptor signaling pathway (Yu et al 2014). Thus, it may be that sesamin can inhibit H1N1-induced PBMCs not only though MAPK inhibition but also via other signaling cascades, which should be further investigated.…”
Section: Discussionsupporting
confidence: 92%
“…These observations were consistent with a previous study, which showed that sesamin downregulated p38 and JNK MAPK signaling pathways via IL-1β-induced human articular chondrocytes (Phitak et al 2012). Moreover, a recent report has shown that andrographolide inhibited the H1N1-infected cell model, while using the H1N1-infected respiratory epithelial cells and coculturing with the immunological cells including the dendritic cells, macrophage, and monocytes, via the RIG-I-like receptor signaling pathway (Yu et al 2014). Thus, it may be that sesamin can inhibit H1N1-induced PBMCs not only though MAPK inhibition but also via other signaling cascades, which should be further investigated.…”
Section: Discussionsupporting
confidence: 92%
“…Andrographolide is well known for its anti-inflammatory effects under various conditions such as cancer and malaria, its antiviral action against infections of the upper respiratory tract and intestinal tract, and its immunomodulatory effects whereby it enhances the expression of cytotoxic T cells and natural killer cells and promotes phagocytosis and antibody-dependent cellmediated cytotoxicity [27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…The results suggest that andrographolide exerts its activity at a post entry step, and effectively inhibits viral genome replication. Several previous studies have shown that andrographolide possesses anti-cancer 30 31 , anti-metastasis 32 , anti-inflammatory 33 , anti-bacterial 34 and antiviral 35 36 37 38 39 40 41 42 43 activities. Andrographolide has been shown to exert activity on a wide range of viruses including human papillomavirus pseudovirus 38 , Influenza A virus 37 43 , hepatitis B virus 36 hepatitis C virus 39 , herpes simplex virus 41 42 and human immunodeficiency virus 35 40 .…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which andrographolide exerts its anti-viral activity remains unknown, although retinoic acid inducible gene-1 (RIG-1)-like receptors 43 and the p38 MAPK/Nrf2 pathway 39 have been proposed as possible targets for the antiviral activity against Influenza A and hepatitis C viruses respectively. However, several studies have proposed that andrographolide exerts anti-cancer activity through an effect on TLR4/NF-kB 31 44 45 46 , and a recent proteomic analysis identified NF-kB as a specific andrographolide binding target 47 .…”
Section: Discussionmentioning
confidence: 99%